Odpowiedź :
Odpowiedź:
1. a) 3x - y + 2 - 5x + 4y - 6 = -2x + 3y - 4
b) 2ab - 4b + 3a - 4a + 2b - 5ab = -a - 3ab - 2b
c) 6x + 18 + 5x - 35 = 11x - 17
d) 3x² - 4x -2x - 2 = 3x² - 6x - 2
e) [tex]\frac{a-12b}{5}[/tex] - [tex]\frac{4a+b}{2}[/tex] = [tex]\frac{2a - 24b}{10}[/tex] - [tex]\frac{20a+5b}{10}[/tex] = [tex]\frac{2a-24b-20a-5b}{10}[/tex] = [tex]\frac{-18a-29b}{10}[/tex]
f) 2x + 14y² - 5x + 15[tex]y^{5}[/tex] = 15
g) 9a - 6b - 3 + 10a - 5b² = 19a - 6b - 5b² - 3
h) x² - 2x + 5x - 10 = x² + 3x - 10
i) 8a² - 8ab + 8ab - 8b² = 8a² - 8b² = 8(a² - b²)
j) - (3x² + 6x - 3x - 6) = -3x² - 6x + 3x + 6 = -3x² - 3x + 6 = -3(x² + x - 2)
2. a) (x × y)/2 = [tex]\frac{1}{2}[/tex]xy
b) (a × b)/2 = [tex]\frac{1}{2}[/tex]ab
c) u × v = uv
d) (x × x)/2 = [tex]\frac{1}{2}[/tex]x²
e) ([tex]\frac{1}{3}[/tex]a × [tex]\frac{1}{3}[/tex]a) = [tex]\frac{1}{9}[/tex]a²
f) 2x = a[tex]\sqrt{2}[/tex]
a = [tex]\frac{2x}{\sqrt{2} }[/tex] = [tex]\frac{2x}{\sqrt{2} }[/tex] × [tex]\frac{\sqrt{2} }{\sqrt{2} }[/tex] = [tex]\frac{2x\sqrt{2} }{2}[/tex] = x[tex]\sqrt{2}[/tex]
Pole = [tex](x\sqrt{2}) ^{2}[/tex] = 2x²